Constitutional Analysis of Executive Power Limitations in Presidential Systems: A Comparative Study of Indonesia and The United States - Harlina Hamid; Nurasia Natsir (Asosiasi Penelitian dan Pengajar Ilmu Hukum Indonesia, 2025)
This research examines the constitutional aspects of executive power limitations in presidential systems by comparing governmental practices in Indonesia and the United States. Through juridical-normative and comparative approaches, this research analyzes constitutional design, jurisprudence, and institutional practices that limit presidential power in both countries. Key findings indicate significant differences in checks and balances mechanisms, with the United States relying on a stricter doctrine of separation of powers compared to Indonesia, which implements power distribution. This research also identifies weaknesses in executive power limitations in Indonesia, particularly concerning legislative authority and the appointment of high-ranking state officials. The results of this research are expected to contribute to strengthening constitutional mechanisms in limiting executive power to prevent abuse of authority.